Gender Disparities in Post-Conflict Societies: A Cross-National Analysis. Issue 3 (3rd July 2021) - Mitra, Aniruddha; Bang, James T.
ABSTRACT: This article investigates the impacts of conflict, resolution, and post-conflict democracy on gender bias. Exploring this question poses two methodological concerns. The first regards selection bias in which countries experience conflict and its resolution. The study addresses this issue using a generalization of the Heckman procedure. The second is that post-conflict democracy is likely endogenous to the level of pre-conflict democracy. This issue is addressed using two-stage least squares. Results show that conflict unambiguously worsens gender outcomes with respect to secondary school enrollment, labor force participation, fertility, and parliamentary representation. However, it does not affect the gap in life expectancy. Conflict resolution improves gender outcomes significantly, but not always by a magnitude that restores pre-conflict levels of equality. Greater post-conflict democratization improves parliamentary representation of women and the gender gaps in life expectancy and secondary school enrollment. However, it worsens the gap in labor force participation. HIGHLIGHTS The study corrects selection bias in conflict and its resolution with a three-step procedure. It instruments for post-conflict democratization using legal origin and geography. Conflict worsens gender inequities in education, the labor force, and representation. Conflict resolution mitigates most conflict-induced inequities, but not fully. Democratization further improves equity in representation and schooling.